SOD-Mimic Cu(II) Dimeric Complexes Involving Kinetin and Its Derivative: Preparation and Characterization - Novotná, Radka; Trávníček, Zdeněk; Herchel, Radovan (Bioinorganic chemistry and applications, 2012)
Two SOD-mimic active dimeric Cu(II) chlorido complexes of the compositions [Cu(2)(μ-HL(1))(4)Cl(2)]Cl(2) (1) and [Cu(2)(μ-HL(2))(2)(μ-Cl)(2)(HL(2))(2)Cl(2)] · 4H(2)O (2) involving the cosmetologically relevant cytokinin kinetin (N6-furfuryladenine, HL(1)) and its derivative N6-(5-methylfurfuryl)adenine (HL(2)) have been synthesized and characterized by elemental analysis, infrared, and electronic spectroscopy, ESI+ mass spectrometry, conductivity and temperature dependence of magnetic susceptibility measurements, and thermogravimetric (TG) and differential thermal (DTA) analyses. The results of these methods, particularly the temperature dependence of magnetic susceptibility, showed the complexes to be dimeric with a strong antiferromagnetic exchange (J = -290 cm(-1) for complex 1 and J = -160 cm(-1) for 2). The complexes have been identified as auspicious SOD-mimics, as their antiradical activity evaluated by the in vitro SOD-mimic assay resulted in the IC(50) values equal to 8.13 μM (1) and 0.71 μM (2).